A meta-synthesis of elite athletes' experiences in dual career development - Li, M.; Sum, R. K. W. (Asia Pacific Journal of Health, Sport and Physical Education, 2017)
Dual career development of elite athletes has gained wide attention in the past two decades. The purpose of this study is to employ a qualitative meta-synthesis method to explore the literature on dual career experiences of elite athletes from 1996 to 2015. A total of nine studies were examined with regard to how elite athletes experience dual careers (combining athletic career with education or work). Inclusion and exclusion criteria were developed during the process to produce a clear statement of applicability of this study. A thematic synthesis was performed and a map of constructs reflected that interpersonal issues played an inter-connected and essential role in influencing elite athletes to a large extent. Potential stakeholders, especially parents and peers, were considered significant targets in implementing support programmes in order to impact the perceptions and feelings of elite athletes towards a dual career. Further research is needed to apply the findings of this study as a conceptual framework for a particular context in which the dual career development of elite athletes is less explored, especially in the context of China.